BUDAYA ORGANISASI DALAM MENINGKATKAN PRESTASI KERJA PEGAWAI DI BALAI DIKLAT APARATUR SUKAMANDI KEMENTERIAN KELAUTAN DAN PERIKANAN - Asep Djaenudin (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
The objective of this research is to understand the organizations culture in improving the performance of employees in Balai Diklat Aparatur Sukamandi. Research was conducted using descriptive methods. Research data collected using a questionnaire completed by 30 employees. Research data analyzed using descriptive technical analysis. Based on the analysis of data obtained the following conclusions: First, perfoemance of employees in Balai Diklat Aparatur Sukamandi relatively good level reached 81.86%. This is shown by how the employees in performing work in a timely manner, have a responsibility in the work, the results show quality of work achieved, to obey the rules, and foster cooperation. Second: organizations culture in Balai Diklat Aparatur Sukamandi relatively low levels reached only 62.98%. This is indicated by the values and norms about the structure of the task, the applicable regulations, the interaction between employees, and appreciation of the achievements that have not been agreed upon in their entirety as a reference in conducting activities to achieve organizational goals, so that should be improved. Third: organizations culture can potentially lead to increase in employee job performance. Agreement on values and norms will encourage the employee organization in conducting the work in accordance with the objectives of the organization. This is indicated particularly by the structure of tasks that employees can demonstrate the quality of the work.